Determination of Phenolic Compounds from Various Extracts of Green Tea by HPLC - Erol, N.T. (Asian Journal of Chemistry, 2013)
Catechins and flavonol glycosides were extracted from green tea with methanol, ethanol and water. Crude extracts derived from green tea were then fractionated using ethyl acetate. After investigation of tea extracts, the following four catechins and three flavonol glycosides were well separated and determined with HPLC analysis i.e., (-)-epigallocatechingallate, (-)-epigallocatechin, (-)- epicatechingallate, (-)- epicatechin, quercetin-3-rhamnosylglucoside, kaempferol-3-rhamnosylglucoside and quercetin-3-glucoside. The content of catechins and flavonol glycosides in green tea extracts varied from 4.27 to 65.46 and 0.06 to 1.66 mg g-1 dry weight tea, respectively, depending on the solvent used. Water was confirmed to be most effective solvent for extracting catechins and flavonol glycosides from green tea.